ATIM-33. INTERIM RESULTS OF A PHASE II MULTI-CENTER STUDY OF ONCOLYTIC ADENOVIRUS DNX-2401 WITH PEMBROLIZUMAB FOR RECURRENT GLIOBLASTOMA; CAPTIVE STUDY (KEYNOTE-192). (11th November 2019) - Aiken, Robert; Chen, Clark; Cloughesy, Timothy; Colman, Howard; Daras, Mariza; Groves, Morris; Khagi, Simon; Kumthekar, Priya; Lang, Frederick; Nassiri, Farshad; Ong, Shirley; Ramakrishna, Rohan; et al.
Abstract: BACKGROUND: DNX-2401 (tasadenoturev) is a replication-competent, tumor-selective, oncolytic adenovirus. Phase I studies in adults with recurrent glioblastoma (rGBM) have demonstrated safety and encouraging clinical activity. A Phase II open-label, dose-escalating multi-center study in rGBM was initiated to evaluate DNX-2401 with pembrolizumab. Planned enrollment of 48 subjects is complete. METHODS: Subjects ≥ 18 years, with a single tumor, KPS ≥ 70% and adequate organ function were enrolled sequentially into 3 cohorts of DNX-2401 (5e8vp, 5e9vp, 5e10vp). A single intratumoral injection of DNX-2401 was administered followed 7 days later by pembrolizumab (200 mg IV). Thereafter, pembrolizumab was infused Q3wks up to 24 months until progression or toxicity. 5e10vp was determined as the optimal dose and this cohort was expanded. Safety monitoring, assessments of response and survival follow-up are ongoing. RESULTS: Nine subjects were treated in the escalation phase; 42 subjects received 5e10vp. No dose-limiting toxicity or unexpected safety issues were identified by an independent review committee, and there were no treatment-related deaths. Adverse events were primarily consistent with underlying disease, effects of the neuro-procedure, expected effects of pembrolizumab, and concomitant use of steroids/anticonvulsants per the standard of care. The majority of events were mild to moderate, and unrelated to DNX-2401. Headache and manageable vasogenic edema were the most common events related to DNX-2401 with pembrolizumab. For the 48 subjects who received pembrolizumab (median 6 cycles), median OS from DNX-2401 administration was 12 months (95% CI, 10.6–14.7), OS6 was 91%, and 47% experienced clinical benefit (stable disease or better). Four subjects (5e10) had a partial response (two with > 94% regression of tumor), and three (5e8; 5e10[2]) are alive > 20 months. Updated safety and efficacy results will be presented. CONCLUSIONS: The data continue to demonstrate that DNX-2401 administered with pembrolizumab has an acceptable safety profile. Long-term survival and clinical benefit remain compelling.